Costly Fees, Men's Participation in Family Planning Declines - Rajindra, Rajindra; Anggraeni, Rasmi Nur (International Journal of Health, Economics, and Social Sciences (IJHESS), 2019)
The Indonesian government, to realize health development through family health improvement priorities, has issued work programs to support the implementation of the matter. One of the government programs implemented at this time is the family planning program. Virile participation in both planning and living in the maintenance of motherhood and child health, including the prevention of motherly mortality, is a still base. Based on this, it is important to know the cause of base masculine participation in planning families. This study aims to analyze the determining factor of participation of men in family planning. This research is a policy study, meaning that research is aimed at obtaining information as a basis for decision-making concerning men's interest factors for enlivening and the planning family. This research was conducted in Donggala County. The population in this study is a man of childbearing age (PUS) located in all regions of Donggala Regency. The analysis used in this study is a frequency tabulation analysis. The study concluded that if you want to use a vasectomy, contraceptive tools should not be decided with a partner, but most of the respondents must be decided with a partner because the contraceptive vasectomy is a family. An effective plan for the childbearing age to prevent pregnancy with a single action, so that there must be a husband's agreement to do already not want any further descendants.